An exploration of South African university students utilization of and engagement with mental health-related information on Instagram - Lekgothoane, Lesego (Department of Psychology, 2023)
Mental health difficulties are prevalent among university students in South Africa and globally, but help-seeking is low due to a variety of structural and attitudinal barriers. It is therefore important to find novel ways of offering mental health information and support through modalities that are both accessible and acceptable to students. Although there has been much concern about the role of social networking sites (SNS) in creating risk for mental health difficulties, SNS are also increasingly being utilized by young adults to access mental health-related content for purposes of education, awareness, and support. However, there has not been any research to date on how university students in South Africa use and engage with mental health-related content on SNS. The current mixed methods study explored South African university students' experiences of accessing and using mental health-related information on Instagram. In the first phase of the study, an online survey was administered to Psychology students (n= 335) at a South African university, exploring use of Instagram to access mental health content. A content analysis was then performed on the ten most commonly accessed mental health-related Instagram accounts listed by survey participants. Finally, seven participants who completed the survey took part in semi-structured interviews to further explore their experiences of using Instagram to access mental health content. A combination of descriptive statistics and thematic analysis was used to analyze data across the three phases. The most common types of mental health content accessed by participants included mental health awareness and psycho-education, inspiration, coping strategies, as well as memes and humour. The most significant qualitative themes from the findings included using Instagram to improve awareness and management of one's own and other people's mental health symptoms, develop better coping mechanisms, find self-care tips, experience connectedness and social support, normalise mental health difficulties and validate and alleviate negative feelings. A small minority of participants reported that accessing mental health-related content on Instagram was unhelpful or triggering. Overall, the findings indicate that Instagram offers an accessible and acceptable source of mental health information, coping strategies, connectedness and validation for participants struggling with mental health issues. Limitations of the study and directions for future research are discussed.